Proposta para planejamento da arborização viária do bairro do Alvinópolis, município de Atibaia - SP - Bagdonas, Natasha Fayer Calegario [UNESP] (Universidade Estadual Paulista (Unesp), 2007)
The urban arborization planning must consider technical criteria, to avoid future conflicts between trees and the urban space, and sociocultural criteria, to satisfy the local population necessities. Considering this principle, the present work proposes an arborization plan for a pilot area enclosing three of the principal streets from Alvinopolis District, county of Atibaia – SP. In order to tackle this objective, requests of tree removal were analyzed to get a panorama of how the subject takes place in the county. After that, promising sites for tree planting were selected in the enclosing area, and urban arborization of the three (3) main streets were retake, proposing necessary substitutions. Finally, 238 residents all over Alvinopolis County have been interviewed, with the objective of appraising their subject sense and focus on environmental education. Then three maps were made: the first one representing characteristics that influence in arborization, the second representing the present arborization and the nine (9) necessary substitutions, and the third representing the plan for the arborization of the pilot area. From the interviewed people, 79% shown themselves favorable to urban arborization, otherwise it does not discard the necessity to inform population about adequate species, county laws and adequate handling of trees.

O planejamento da arborização urbana deve levar em conta critérios técnicos, para evitar futuros conflitos entre as árvores e o espaço urbano, e socioculturais, para satisfazer as necessidades da população local. Tendo esse princípio como base, o presente trabalho propõe um planejamento para a arborização de uma área piloto abrangendo três das principais vias do Bairro do Alvinópolis, município de Atibaia – SP. Para tanto, foram analisados pedidos de remoção de árvores, obtendo-se um panorama de como o assunto é tratado no município. Em seguida foram selecionados na área piloto locais propícios para o plantio de árvores, e a arborização das três vias foi recenseada, propondo substituições necessárias. Finalmente 238 moradores de todo o bairro foram entrevistados, com o objetivo de avaliar sua percepção sobre o assunto e direcionar ações de educação ambiental. Foram confeccionados três mapas: um representando características que influenciam na arborização, um representando a arborização atual e as nove substituições necessárias e um representando o plano de arborização da área piloto. Das pessoas entrevistadas, 79% mostraram-se favoráveis à arborização urbana, o que não descarta a necessidade de informar a população sobre espécies adequadas, legislação municipal e manejo adequado das árvores.
Keywords: Educação ambiental; Arborização urbana; Urban arborization; Environmental education